Balance scorecard (BSC): Incorporating "Key performance indicators" (KPI) in the Evaluation of the Healthcare System - Khan, Sikandar Hayat; Kureshi, Nadeem; Aslam, Muhammad Sohail; Rafique, Sibtain (Pakistan Armed Forces Medical Journal, 2023)
Using the balanced scorecard approach, Strategic Management Initiative (SMI) driven Key Performance Indicators (KPIs) have allowed measurable data regarding various clinical, medical, patient and logistic outputs for healthcare leadership to manage an ongoing improvement system in real-time. We underwent a comprehensive search to have 168 articles with the keywords "Balanced Scorecard in healthcare". We applied filters for the last ten years only. We shortlisted 14 studies. The study highlighted various KPIs utilised in different healthcare settings, with most authors favouring BSC methodology as a comprehensive strategy to deal with multi-dimensional hospital processes. The most utilised KPIs included service quality, patient safety, increased healthcare literacy, empowering patients, developing the empathic attitude and social skills in medical staff, professional human resource management and financial management and interests of stakeholders. In short, the BSC strategy is suggested for implementation to improve healthcare-related processes.